Sound effects: the effects of sound-producing toys on the level of social and cognitive play in 3, 4, and 5-year-olds - Turpin, Jenette Katherine (Kansas State University, 2008)
This study investigated the effects of sound-producing toys on the social and cognitive levels of play in young children. Thirty-four pairs of children were observed (N=68), ages 3, 4, and 5 years, during 15-minute play sessions. The play conditions were: 1) farm set with sound, 2) farm set with no sound, 3) doctor set with sound, and 4) doctor set with no sound. Independent variables included age, gender, and the presence or absence of sound. Dependent variables included the percentages of time that children engaged in levels of social play (solitary, parallel, and group), levels of cognitive play (functional, constructive, and dramatic), and non-play. Overall, sound was marginally associated with more time spent in play. For group play there was a marginally significant sound by gender interaction, suggesting that sound doubled female group play. There was a significant sound by age interaction suggesting that 5-year olds engaged in group play more with sound than with no sound. A significant sound by gender interaction indicated that the presence of sound increased dramatic play in both males and females, but more so in females. A sound by age interaction indicated that 5-year-olds engaged in more dramatic play with sound than without. Three-year-olds also engaged in more dramatic play when sound was present. There was a significant sound by gender interaction indicating males engaged in more functional play than girls when sound was present. There was a significant sound by age interaction, indicating that 5-year-olds engaged in less constructive play when sound was present. In conclusion, young children were more likely to engage in play when sound was present. Sound enhanced the play of 5-year-olds who engaged in more group and dramatic play, but less constructive play, with sound-producing toys. Sound also enhanced the play quality of 3-year-olds, who engaged in more dramatic play when sound was present. Furthermore, sound enhanced the play of girls who engaged in more group and dramatic play with sound, and boys, who engaged in more dramatic play with sound. Limitations of the study along with implications for future research are discussed.
Keywords: Early childhood; Environment design; Toys; Early childhood education; Preschool; Sound; Education, Curriculum and Instruction (0727); Education, Early Childhood (0518)